A intersecção entre literatura, memória e história em Reading in the dark, de Seamus Deane - Poiana, Fernando Aparecido [UNESP] (2015)
This study analyses the intersection between literature, memory and history in Seamus Deane's Reading in the Dark. To do so, it uses Walter Benjamin's notions of memory, experience and history, and discusses the hypothesis that there is an intersection between literature and history in Deane's novel that is created by the use it makes of memory as its central narrative procedure. The analysis of the aesthetic elements of this novel in parallel with the historical context out of which it is written and with which it establishes a dialogue will reveal in the end that history is an intrinsic feature of Reading in the Dark, in a way that Deane's fiction has not only an aesthetic but also an ethical dimension to it